« J’ai bien connu Sankara... » Un ancien fonctionnaire algérien se souvient - Chloé Maurel (Cahiers d’histoire.)
International civil servant Djilali Benamrane, an Algerian economist, worked for the UN in Africa, and made the acquaintance of Burkina Faso President Thomas Sankara. In this interview, he recalls his memories about Thomas Sankara, his style of management, his leadership, his socialist convictions, his positive action for his country, his great popularity among the peoples of his country, and his tragic murder.